Effects of Urea application and Cytokinin Spray , on some charac-teristics of Grape Transplant .( Vitis vinifera L.) .: Loay M. Hamza Hadi K. Hussien - كاظم حسين الجبوري, هادي; محمد حمزه المعموري, لؤي (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted at Horticulture Department – College of Agriculture AL-Qasim Green University of during the period 27/3/2016 – 15/7/2016 to study the effect Urea application at (0 , 2, 4 , 8. Gseedling-1) and Spray of Cytokinin ( 0 , 25 ,50 , 100 mg. L-1) on some characteristics of grape Transplants. The results indicated that adding Urea and alone or in combination treatment caused a significant increasing in the rate of length of branches Total chlorophyll content in leaves and number of the plants branches . while the character of N content in leaves was not significant in Cytokinin spray treatment and character of root length the treatment of 4 Urea gm .Seedling-1 was superior as compared with others with 12.60 cm .The treatment of Urea 8 g.seedling-1 and Cytokinin at the level 100 mg.L-1 show the highest rate of those characteristics compared to control treatment .